Ketahanan dan Kebangkitan: Strategi Pemasaran Terpadu Ditengah Pandemi Covid-19 - Latif Ahmad Fauzan; Augustin Mustika Chairil (Jurnal Spektrum Komunikasi, 2024)
The Covid-19 pandemic has had a significant impact on the MSME (Micro, Small and Medium Enterprises) sector. Although the pandemic has caused most sectors to experience huge losses, SFC Dobel Tree as one of the MSMEs in Bojonegoro Regency is able to survive and be able to develop its business until after the pandemic. The right marketing strategy is important for MSMEs to maintain their existence. Therefore, this study was conducted to evaluate the Marketing Mix Strategy used by SFC Dobel Tree after the Covid-19 pandemic. The purpose of this study is to describe the Marketing Mix carried out by SFC Dobel Tree after the Covid-19 pandemic. This research uses a qualitative descriptive method with interview techniques and direct observation. The results showed that SFC Dobel Tree implemented through segmenting, targeting, and positioning (STP) to target its target market and implemented its marketing strategy by establishing a marketing mix and successfully overcoming challenges during the Covid-19 pandemic. The strategy includes product, promotion, people, process and physical evidence.